Influence of prebreeding progesterone plus prostaglandin F2-alpha on estrus and fertility in lactating dairy cows - Mee, M.O.; Stewart, R.E.; Stevenson, Jeffrey S.; Call, Edward P. (Kansas Agricultural Experiment Station, 2012)
Progesterone administered before breeding may increase estrous expression and subsequent fertility in lactating dairy cows. Holstein cows (n=302) were assigned randomly at calving to three groups. Cows received no treatment (controls), one injection of prostaglandin F 2-alpha (PGF), or progesterone plus one injection of PGF (PRID + PGF). The average interval to estrus was 5 days shorter in PRID + PGF cows compared to cows given only PGF. In addition, more cows were observed in estrus 2 to 5 days after treatment in the PRID + PGF group compared to the PGF group. Average days from calving to conception were reduced in PRID + PGF cows by 15 to 20 days compared to control and PGF cows. We concluded that prebeeding progesterone in combination with PGF appears to enhance fertility.
Keywords: Dairy; Progesterone; Prostaglandin F2-alpha; Fertility; Lactation